Effect of Applied Tensile Stress on Hydrogen-Induced Delayed Fracture Mode of Fe-Ni-Cr Austenitic Alloy Weldment - Yingjie Yan; Yukun Zhang; Lixian Zhao; Yongqing Chen; Rui Cao; Honghui Wu; Yang He; Yu Yan; Lijie Qiao (Metals, 2022)
Fe-Ni-Cr austenitic alloys are widely used in hydrogen environments as structural materials. Their weld normally shows higher hydrogen-embrittlement sensitivity than the base metal, endangering large-scale applications. Herein, by using electron microscopy and numerical calculations, the influence of applied load on the fracture mode of hydrogen-embrittled JBK-75 alloy weldment is revealed and correlated with a competition between hydrogen-prompted intergranular decohesion (HPID) and hydrogen-enhanced localized plasticity (HELP). Therefore, independent of the load levels, the weld featuring a lower strength and smaller grain sizes is always more vulnerable to hydrogen embrittlement than the base metal.